Impact of osteopenia and osteosarcopenia on the outcomes after surgery of hepatobiliary-pancreatic cancers - Wang, Xiaofeng; Wu, Min; Liu, Qian; He, Wei; Tian, Yong; Zhang, Yan; Li, Cuiping; Liu, Yanni; Yu, Anqi; Jin, Hongyan (Frontiers in Oncology, 2024)
The purpose of this study is to investigate potential associations between osteopenia, osteosarcopenia, and postoperative outcomes in patients with hepatobiliary-pancreatic cancer (HBPC). Methods: Three online databases, including Embase, PubMed, and the Cochrane Library, were thoroughly searched for literature describing the relationship between osteopenia, osteosarcopenia, and outcomes of surgical treatment of HBPC patients from the start of each database to September 29, 2023. The Newcastle-Ottawa Scale was used to rate the quality of the studies. Results:This analysis included a total of 16 articles with a combined patient cohort of 2,599 individuals. The results demonstrated that HBPC patients with osteopenia had significantly inferior OS (HR: 2.27, 95% CI: 1.70-3.03, p < 0.001) and RFS (HR: 1.96, 95% CI: 1.42-2.71, p < 0.001) compared to those without osteopenia. Subgroup analysis demonstrated that these findings were consistent across univariate and multivariate analyses, as well as hepatocellular carcinoma, biliary tract cancer, and pancreatic cancer. The risk of postoperative major complications was significantly higher in patients with osteopenia compared to those without osteopenia (OR: 1.66, 95% CI: 1.19-2.33, p < 0.001). Besides, we also found that the presence of osteosarcopenia in HBPC patients was significantly related to poorer OS (HR: 3.31, 95% CI: 2.00-5.48, p < 0.001) and PFS (HR: 2.50, 95% CI: 1.62-3.84, p < 0.001) in comparison to those without osteosarcopenia. Conclusion: Preoperative osteopenia and osteosarcopenia can predict poorer OS and RFS with HBPC after surgery.